Comparative Analysis of Water Injection Patterns and Rates for Oil Recovery Optimization in a Mature Reservoir - Wibowo, Djunaedi Agus; Rahmawan, Sigit; Sabirey, Adrian Maulana; Andrianaivo, Lala (Penerbitan Universitas Trisakti, 2026)
Waterflooding is one of the most widely applied secondary recovery methods to maintain reservoir pressure and improve oil recovery in mature oil fields. However, ineffective injection patterns and non-optimal injection rates may reduce sweep efficiency and accelerate water breakthrough. Therefore, this study aims to evaluate and optimize waterflood injection patterns and injection rates in Layer Y of Field X using dynamic reservoir simulation with tNavigator. The study employed a full-field black-oil simulation model involving data preparation, model initialization, history matching, and production forecasting under several development scenarios. The evaluated scenarios included base case, infill drilling, and water injection using 3-spot, 5-spot, and 7-spot injection patterns with different injection rates. This study applied the integration of comparative injection-pattern analysis with injection-rate optimization using a validated full-field simulation model for a mature reservoir. The initialization and history matching results showed good agreement between the simulation model and historical field data, indicating that the model was reliable for forecasting purposes. The simulation results demonstrate that waterflood implementation significantly improved reservoir performance compared with the base case and infill drilling scenarios. Among all evaluated cases, the 5-spot injection pattern with an injection rate of 1000 STB/day produced the best performance, achieving a cumulative oil production of 97.36 MMSTB and a recovery factor of 46.76%. The study confirms that optimizing injection pattern geometry and injection rate plays an important role in improving sweep efficiency and maximizing oil recovery in mature reservoirs.